Age Management in the Public Sector - Intergenerational Learning Strategy - Warwas, Izabela (Studia Oeconomica Posnaniensia, 2016)
The article deals with the management of older workers, a critical issue in present-day organisations. A theoretical discussion of age management practices is followed by a description of the major changes in management practices taking place in the public sector in Poland. The main part of the article presents the results of a study in age management in the public and non-public sectors in Poland, which was conducted from 2011 to 2015 using the triangulation of research methods and data sources. The most important findings of the three-step research process concern the use of age management tools, the knowledge-retention methods applied in organisations, the training process, and the assignment of tasks and work within intergenerational teams. The inference process is enhanced by the results of other domestic and international studies. The general conclusion derived from the study is that the public sector and non-public sector is not significantly different in terms of the age management practices they use.